Investigation on the response of anaerobic membrane bioreactor to temperature decrease from 25 °C to 10 °C in sewage treatment. (November 2017) - Watanabe, Ryoya; Nie, Yulun; Wakahara, Shinichiro; Komori, Daisuke; Li, Yu-You
Graphical abstract: Highlights: Response of AnMBR to temperature decrease 25–10 °C in sewage treatment was studied. Only 53% and 32% of COD was recovered as CH4 at 10 °C at HRT 24 h and 16 h. Low temperature caused a higher membrane fouling rate by pore blocking. Inhibition to hydrolysis and acidification step lead to decreased efficiency at 10 °C. Abstract: Anaerobic membrane bioreactor (AnMBR) for sewage treatment was operated for 650 days with the decrease of temperature from 25 °C to 10 °C. At higher temperature >15 °C, COD removal was above 94% while sewage treatment efficiency and relevant CH4 production decreased below 15 °C. The effluent COD at 10 °C was 134 mg/L at HRT of 16 h. Moreover, low temperature can result in a higher membrane fouling rate due to the microbial self-protection behavior in coping with the temperature decrease by releasing soluble microbial products (SMP) and extracellular polymeric substances (EPS). The contribution of pore blocking to membrane fouling caused by protein from SMP and EPS increased from 17% to 45% and that of cake layer decreased from 81% to 53% at 25 °C and 15 °C respectively. The inhibition to hydrolysis and acidification process was responsible to the decrease of sewage treatment at lower temperature.